Re-treatment with abatacept plus methotrexate for disease flare after complete treatment withdrawal in patients with early rheumatoid arthritis: 2-year results from the AVERT study - Daniel E Furst; Paul Emery; Gerd R Burmester; Vivian P Bykerk; Bernard G Combe; Michael A Maldonado; Tom WJ Huizinga (RMD Open)
Objectives To complete reporting of outcomes after total withdrawal of all rheumatoid arthritis (RA) therapy and re-treatment after flare in Assessing ﻿Very Early Rheumatoid arthritis Treatment study (NCT01142726).Methods Patients with early RA were initially randomised to double-blind, weekly subcutaneous abatacept plus methotrexate, or abatacept or methotrexate monotherapy. At month 12, patients with Disease Activity Score (DAS)28 C reactive protein (CRP) <3.2 had all RA treatments rapidly withdrawn and were observed for ≤12 months or until flare. After ≥3 months’ withdrawal, patients with protocol-defined RA flare received open-label abatacept plus methotrexate for 6 months (re-treatment).Results  Proportion of patients in DAS28-CRP–defined remission remained numerically higher in original abatacept plus methotrexate and abatacept arms versus methotrexate arm up to day 253 of withdrawal. At the end of the withdrawal period, few patients remained in remission across all arms: 9/73 (12.3%), 7/50 (14.0%) and 6/53 (11.3%), respectively. For patients entering re-treatment, after 6 months’ re-treatment, 95/124 (76.6%) and 78/124 (62.9%) patients achieved DAS28-CRP <3.2 and <2.6, respectively; mean changes in DAS28-CRP and Health Assessment Questionnaire–Disability Index scores from re-treatment baseline were –2.87 and 0.76, respectively. Re-treatment was well tolerated; exposure-adjusted infection rates per 100 patient-years were lower with abatacept plus methotrexate during withdrawal (7.2) and re-treatment (17.2) versus initial treatment periods of months 0–6 (116.6) and 6–12 (64.6).Conclusions Most patients flared within 6 months of therapy withdrawal and few sustained major responses for 1 year. Re-treatment with abatacept plus methotrexate was effective and well tolerated in this controlled setting.